35.7k views
2 votes
If f(x) = 3x - 1 and g(x) = x + 2, find (f +9)(x).

O A 2-1
O B 4x+1
OC 2-3
O D. 3x-3
SUB

2 Answers

3 votes

Answer:

(f+g)(x)=4x+1

Explanation:

This question asks us to find (f+g)(x), which is equal to adding f(x) and g(x).

f(x)+g(x)

We know that f(x) is 3x-1 and g(x) is x+2.

f(x)=3x-1

g(x)= x+2

(3x-1)+(x+2)

Combine like terms. Add all the terms with a variable, then all the terms without a variable.

(3x+x)+(-1+2)

(4x)+(-1+2)

(4x)+(1)

4x+1

(f+g)(x)=4x+1

User Thomas Rollet
by
4.8k points
4 votes

Answer:

4x +1

Explanation:

f(x) = 3x - 1

g(x) = x + 2,

(f +g)(x)= 3x-1 + x+2

Combine like terms

=4x +1

User Radhwane Chebaane
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.